MODEL OF STRATEGIC PARTNERSHIP IN HEALTHCARE SERVICE INNOVATION AT HOSPITAL IN BANDUNG, WEST JAVA, INDONESIA - Huraerah, Abu (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
The study aims to describe the patient's response to healthcare service at the hospital, innovative strategies for healthcare service at the hospital, and model of strategic partnership in healthcare service innovation at a hospital. This research uses qualitative research method. Data analysis as consisting of three concurrent flows of activity: data reduction, data display and conclusion drawing and verification. Meanwhile, this research uses a data collection method that is the in-depth interview, observation and document study. The patient's response to healthcare service at hospital: (1) patients expect quality healthcare service, (2) patients want the ease and comfortable in healthcare service and (3) patients assume that hospitals have to be able to deliver better quality service to provide satisfaction. Innovative strategies of healthcare service: (1) investments in health facilities, (2) development of health human resources, (3) improving healthcare service mechanism, (4) the functioning of private clinics, (5) quality and cost control and (6) healthcare service should not only rehabilitative-curative, but also preventive-promotive. Model of strategic partnership in healthcare service innovation at hospitals, namely the involvement of stakeholders, such as local government, hospital, Health Social Security Agency or BPJS Kesehatan (Badan Penyelenggara Jaminan Sosial Kesehatan), and the community (patient).